Розробка сюжету, референсів та механік ігрового контенту «Легенда загубленого скарбу» - Карабут, А. О.; Міщенко, А. А. (ХНУРЕ, 2024)
In the course of the work, the storyline of the game "Legend of the Lost World" was developed, covering an exciting story that unfolds in a dense, mysterious jungle. The player acts as an archaeologist who embarks on a dangerous expedition in search of a lost treasure that hides a legendary lost world. With a key element of uncovering mysteries and solving puzzles, the player explores different locations, interacts with local tribes and encounters mysterious characters.
Keywords: «Легенда загубленого скарбу»; сюжет ігрового контенту